Activity Testing Of Katuk Leaf Ethyl Acetate Fraction Gel Preparation (Sauropus Androgynus (L.) Merr.) On Healing Wistar Strain White Rat Burns - Mintarti; Juvita Herdianty (Universitas STRADA Indonesia, 2023)
Burns are a condition of loss or damage to skin tissue due to contact between the skin and a heat source. The ethyl acetate fraction of katuk leaves (Sauropus Androgynus (L.) Merr.) is known to be able to help accelerate the healing process of burns because it contains flavonoids, alkaloids, tannins and saponins. The purpose of this study was to analyze the effect of giving the ethyl acetate fraction of katuk leaves and to find out the best concentration of the fraction in healing burns. This study was a laboratory experimental study using the Post Test Control Only Group Design approach using 25 male white rats divided into 5 groups (each group consisted of 5 rats). The treatment groups were K+ (bioplacenton), K- (base), the ethyl acetate fraction of katuk leaves which consisted of several concentrations, namely F I (5%), F II (10%), F III (20%). The parameters observed were a decrease in the diameter of the burn wound and healing of the skin of the rats. Based on the results of observations of healing of burns, statistically showed a significant difference between groups with a p value <0.05. The best concentration in healing burns on the rat's back was a concentration of 20% with a healing percentage of 83.11%, followed by a concentration of 10% (66.71%), a concentration of 5% (56.00%). The healing activity of burns in the positive control with a healing percentage of 82.35%. So the best burn healing activity was in the ethyl acetate fraction of katuk leaves with a concentration of 20% with a healing percentage of 83.11%.